2017
DOI: 10.3390/rs10010040
|View full text |Cite
|
Sign up to set email alerts
|

Land Subsidence in Chiayi, Taiwan, from Compaction Well, Leveling and ALOS/PALSAR: Aquaculture-Induced Relative Sea Level Rise

Abstract: Chiayi County is located in the largest alluvial plain of Taiwan with extensive aquaculture and rice farming sustained by water extracted from groundwater wells. Chiayi is a typical aquaculture area affected by land subsidence, yet such lands worldwide combine to provide nearly 90% of global aquaculture products, greatly reducing oceanic overfishing problems. This study uses precision leveling, multi-layer compaction monitoring well (MLCW) and spaceborne SAR interferometry (InSAR) to examine the cause and effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…As tide gauges measure relative SLR with reference to a tidal benchmark grounded on the adjacent coast, even minor ground motions will significantly affect sea level height measurements. Previous studies have reported on vulnerable sites for coastal subsidence and short-term sea level rise, including Hampton Roads, Virginia [14], New York City [15], Taiwan [16], and North Carolina [17]. Hence, the estimation and correction of the local ground motion at and around the tide gauges is important to minimize uncertainties in the local and global sea level changes observed [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As tide gauges measure relative SLR with reference to a tidal benchmark grounded on the adjacent coast, even minor ground motions will significantly affect sea level height measurements. Previous studies have reported on vulnerable sites for coastal subsidence and short-term sea level rise, including Hampton Roads, Virginia [14], New York City [15], Taiwan [16], and North Carolina [17]. Hence, the estimation and correction of the local ground motion at and around the tide gauges is important to minimize uncertainties in the local and global sea level changes observed [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For the feasibility of this study, Sentinel-1A Interferometric SAR data has been collected from Alaska Satellite Facility website (https://vertex.daac.asf.alaska.edu) and the DORIS data of Verified Orbit has collected from the European Space Agency website (https://qc.sentinel1.eo.esa.int/aux_poeorb/) which is available 20 days after the actual satellite acquisition. Generally, the perpendicular baseline and time difference between the images are important in such land subsidence-related studies because several attempts have been done in different areas with different spatial baselines to find an identical rate of subsidence [19,21]. The distance between the two SAR image acquisitions represents a baseline, hence, there are three spatial baselines 110, 136, and 121 m and three temporal baselines of 108, 102 and 120 days for the years 2017, 2018, and 2019 respectively.…”
Section: Data and Methodsologymentioning
confidence: 99%
“…Nevertheless, this technique indeed provides a scope of rapid assessment of land subsidence over a large region. The occurrence of land subsidence has been studied in many places around the world, including Tokyo in Japan [13], Mexico city in Mexico [14], western Saudi Arabia [15], Jakarta in Indonesia [16], Ravenna in Italy [17], Bangkok in Thailand [18], Pingtung plain in Taiwan [19], Beijing in China [20] etc. In the Indian context few cities such as Delhi [21], Kolkata [11,22], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The Persistent Scatterers Interferometry (PSI) techniques (e.g. Ferretti, Prati, & Rocca, 2001;Berardino et al, 2002;Hooper et al, 2004;Ferretti et al, 2011) have been successfully adopted for a wide range of applications in disaster management, and it has extensively proven to be a valuable tool to detect ground deformations due to landslides (Solari et al, 2018;Del Soldato, Riquelme, et al, 2018a;Ciampalini et al, 2016) or subsidence (Bonì et al, 2017;Da Lio & Teatini, 2018;Gao et al, 2018;Hung et al, 2017;Minh, Van Trung, & Toan, 2015;Aslan, Cakır, Ergintav, Lasserre, & Renard, 2018;Sun et al, 2017) or infrastructures stability (Di Pasquale et al, 2018).…”
Section: Introductionmentioning
confidence: 99%